La sintassi dell’infinito preceduto da un determinante: presente e (un po’ di) storia - Szilágyi, Imre (Verbum – Analecta Neolatina, 2025)
In this paper we present the syntax of the construction called infinitive preceded by a determinant both in modern Italian and in the Florentine language of about four centuries ago. During the syntactic analysis concerning modern Italian, we describe the various syntactic criteria on the basis of which the three structural subtypes can be identified, and we also seek the answer to the question whether examples can be found that contradict the syntactic theory exposed. As regards the analysis of the construction in the stage examined of the Old Florentine language, we show, on the one hand, that the subtypes identified in Modern Italian can also be traced to this stage of the language. On the other hand, we illustrate with various examples that some syntactic changes occurred over time, particularly in the expression of the subject and the direct object of the infinitive.